Isolasi Cendawan Mikoriza Arbuskula dari Rizosfer Tanaman Berkayu Asal Pulau Bangka dan Karakteristik Struktur Kultur Mikorizanya: Isolation of Arbuscular Mycorrhizal Fungi from Rhizosphere of Bangka Island Woody Plants and their Mycorrhizal Structure Culture Characteristics - Nampiah Sukarno; Cici Rahmawati; Sri Listiyowati; Wendi Nurul Fadillah; Yanti Novera (Jurnal Sumberdaya Hayati, 2023)
Arbuscular Mycorrhizal Fungi (AMF) associate with a variety of plants including forest trees. Research on AMF in forestry in Indonesia is limited, especially on woody plants grown in Bangka Island. Therefore, the aim of this research was to isolate and identify AMF associated with woody plants from Bangka Island grown in the post-mining soil in greenhouse for 7 years. The Soil samples derived from 8 pots of the 7 years old woody plants were used as spore sources. Spore extraction from the soil used the wet sieving and decanting method. Fungal identification was carried out based on morphological characteristics, and fungal isolation used pot culture with Pueraria javanica as a host plant. Fungal structures within the root were analyzed after root staining with trypan blue. There were 18 spore morphotypes observed which belong to 5 types of Acaulospora and 13 types of Glomus. Seven single spore pot cultures were successfully isolated from species of Acaulospora sp.1, Acaulospora sp.4, Acaulospora sp.5, Glomus sp.2, Glomus sp.3, Glomus sp.6, and Glomus sp.11. AM fungal colonization structures observed within the root were Paris type arbuscules, internal hyphae, and vesicles. The AMF cultures obtained could be used as biofertilizer for woody plant seedlings production for post mining reclamation activities.